2021
DOI: 10.3389/fmicb.2021.681911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Metronidazole Resistance in Helicobacter pylori

Abstract: Efficacy of Helicobacter pylori (H. pylori) eradication therapy has declined due to rapid rises in antibiotic resistance. We investigated how increased temperature affected H. pylori (NCTC 11637) growth and its sensitivity to metronidazole in vitro. We performed transcriptomic profiling using RNA-sequencing to identify differentially expressed genes (DEGs) associated with increased temperature. Transcriptional pathways involved in temperature-driven metronidazole resistance changes were analyzed through bioinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“… 1 , 8 The increasing prevalence of antibiotic resistance is our main concern in treatment of H. pylori infection, which can lead to significant eradication failure. 9 , 10 In China, the resistance rates to clarithromycin, metronidazole, and levofloxacin, are already high. One study from Nanjing showed that the H. pylori resistance rates to clarithromycin, levofloxacin and metronidazole were 47.03%, 33.59% and 80.76%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 8 The increasing prevalence of antibiotic resistance is our main concern in treatment of H. pylori infection, which can lead to significant eradication failure. 9 , 10 In China, the resistance rates to clarithromycin, metronidazole, and levofloxacin, are already high. One study from Nanjing showed that the H. pylori resistance rates to clarithromycin, levofloxacin and metronidazole were 47.03%, 33.59% and 80.76%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the first studies to examine the transcriptomic perturbations associated with zinc acetate treatment, which showed distinct gene expression profiles compared to controls. Widespread transcriptomic perturbations were also previously seen after changes in environmental conditions such as temperature ( 17 , 18 ). This suggests significant transcriptomic changes occur in H. pylori in response to biophysical as well as chemical perturbations.…”
Section: Discussionmentioning
confidence: 76%
“…Mutations in the rdxA gene encoding oxygen-insensitive nitroreductase and in the frxA gene encoding flavin oxidase reductase are the main cause of resistance to metronidazole. Mutations in these genes reduce the ability of metronidazole to recover to active forms (NO 2− , NO 2 2− ), which have a damaging effect on the bacterial DNA structure [14,15]. Levofloxacin is a fluoroquinolone, which acts via its interaction with DNA gyrase encoded by the gyrA and gyrB genes.…”
Section: Characteristics Of H Pylori Antibiotic Resistancementioning
confidence: 99%